Altered White Matter and Layer VIb Neurons in Heterozygous Disc1 Mutant, a Mouse Model of Schizophrenia - Tsai, Shin-Hwa; Tsao, Chih-Yu; Lee, Li-Jen (Frontiers in Neuroanatomy, 2020)
Increased white matter neuron density has been associated with neuropsychiatric disorders including schizophrenia. However, the pathogenic features of these neurons are still largely unknown. Subplate neurons, the earliest generated neurons in the developing cortex has also been associated with schizophrenia and autism. The link between these neurons and mental disorders is also not well established. Since cortical layer VIb neurons are believed to be the remnant of subplate neurons in adult rodent brain, in this study, we aimed to examine the cytoarchitecture of neurons in cortical layer VIb and the underlying white matter in heterozygous Disc1 mutant (Het) mice, a mouse model of schizophrenia. In the white matter, the number of NeuN-positive neurons was quite low in the external capsule; however, the density of these cells was found increased (54%) in Het mice compared with wildtype (WT) littermates. The density of PV-positive neurons was unchanged in the mutants. In the cortical layer VIb, the density of CTGF-positive neurons increased (21.5%) in Het mice, whereas the number of Cplx3-positive cells reduced (16.1%) in these mutants, compared with WT mice. Layer VIb neurons can be classified by their morphological characters. The morphology of Type I pyramidal neurons was comparable between genotypes while the dendritic length and complexity of Type II multipolar neurons were significantly reduced in Het mice. White matter neurons and layer VIb neurons receive synaptic inputs and modulate the process of sensory information and sleep/arousal pattern. Aberrances of these neurons in Disc1 mutants implies altered brain functions in these mice.